THE EFFECT OF WORK SPIRIT AND WORK CULTURE ON THE PERFORMANCE OF EMPLOYEES IN THE SERVICE OF TRANSPORTATION - Trisnowati Josiah (Saburai International Journal of Social Sciences and Development, 2020)
Research to be conducted kind of research is descriptive. This research is a study that intends to make the exposure of the systematic, factual, and accurate information on the facts and the properties of a particular population. This study using 33 survey respondents. From  the  data  processing  has  successfully  found  an  answer  hypothesis  that  is  as follows; there are significant Morale (X1) on employee performance (Y), with the level of influence (R-square) of 95.9%, which means Morale of 95.9% impact on employee performance. There is the influence of the working antarabudaya (X2) with employee performance (Y), with the level of influence of 91.3%, which means that the work culture at 91.3% influence on employee performance. There is the influence of Morale (X1), work culture (X2) with employee performance (Y), with the level of influence of 95.9%, which means that the Morale and work culture influence by 95.9% on employee performance.